2017
DOI: 10.24099/vet.arhiv.160513
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal influence on airborne dust and endotoxin concentrations in a laying hen house

Abstract: In the present study, air quality in a cage-housed laying hen house was investigated throughout the seasons by assessing dust and endotoxin concentrations. Measurements were done twice a month during the 1-year production cycle. The mean levels of dust and endotoxins ranged from 0.60 mg/m 3 in May to 2.83 mg/m 3 in November, and from 203.15 EU/m 3 in August to 745.53 EU/m 3 in April. Significantly higher concentrations of dust and endotoxins in the poultry house were determined in the autumn and winter seasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…Dust concentration yielded a significant positive correlation with bacterial count in the air (r = 0.602; p < 0.05) (Table 2). The total bacterial count in the broiler house air was consistent with the results reported by Vučemilo et al [45] and Matković et al [46], whereas higher values have been reported by Saleh et al [30], Wójcik et al [31], Lawniczek-Walczyk et al [32], Oppliger et al [37], and Haas et al [47]. In our study, the median bacterial count was significantly higher (p < 0.001) in winter (5.70 × 10 4 CFU/m 3 ) than in summer (4.13 × 10 4 CFU/m 3 ) (Table 1), which is consistent with the results reported by Saleh et al [30] and Wójcik et al [31] but opposite to the results reported by Lawniczek-Walczyk et al [32] and Chen et al [33].…”
Section: Parameter Summer Wintersupporting
confidence: 91%
“…Dust concentration yielded a significant positive correlation with bacterial count in the air (r = 0.602; p < 0.05) (Table 2). The total bacterial count in the broiler house air was consistent with the results reported by Vučemilo et al [45] and Matković et al [46], whereas higher values have been reported by Saleh et al [30], Wójcik et al [31], Lawniczek-Walczyk et al [32], Oppliger et al [37], and Haas et al [47]. In our study, the median bacterial count was significantly higher (p < 0.001) in winter (5.70 × 10 4 CFU/m 3 ) than in summer (4.13 × 10 4 CFU/m 3 ) (Table 1), which is consistent with the results reported by Saleh et al [30] and Wójcik et al [31] but opposite to the results reported by Lawniczek-Walczyk et al [32] and Chen et al [33].…”
Section: Parameter Summer Wintersupporting
confidence: 91%